2021
DOI: 10.1186/s12935-021-02067-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer properties of quercetin in osteosarcoma

Abstract: Osteosarcoma is a primary bone tumor. Although it is a rare disease in general, it is the most common primary bone tumor among children. Despite the significant advances made in the field of osteosarcoma treatment, the outcomes of this disease are still unfavorable. Besides, there is still no targeted therapy for osteosarcoma that can be used in clinical settings. Quercetin is a member of the phytochemical family which is used for different diseases including cardiovascular diseases, diabetes, and cancer. Its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Que has been proven to have anticancer properties, and its bioavailability is limited by poor water solubility. 9,45–54 It is significant to develop drug carriers to improve the bioavailability of Que. The Que-loaded micelles were prepared by dialysis method in PBS (1×, pH = 7.4) first.…”
Section: Resultsmentioning
confidence: 99%
“…Que has been proven to have anticancer properties, and its bioavailability is limited by poor water solubility. 9,45–54 It is significant to develop drug carriers to improve the bioavailability of Que. The Que-loaded micelles were prepared by dialysis method in PBS (1×, pH = 7.4) first.…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin can influence the development of tumor by regulating epigenetics, which can directly regulate the expression of miRNA and the level of DNA methylation to exert an anticancer effect and enhance the sensitivity of tumor cells to chemotherapy [ 36 ]. Quercetin has a significant antitumor effect in osteosarcoma [ 40 ]. There is evidence that the possibility of using quercetin as a therapeutic option for glioblastoma multiforme [ 41 ].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Quercetin is one of the main flavonoids. Some recent studies have shown that quercetin promotes osteoblast differentiation [ 90 , 91 , 92 , 93 ]. Moreover, several flavonoids, including icaritin [ 94 , 95 , 96 , 97 , 98 ], genistein [ 99 , 100 , 101 , 102 ] and kaempferol [ 103 , 104 , 105 ], have been shown to promote osteogenic differentiation by regulating the expression of Runx2 and BMP-2 differentiation through their estrogenic effects.…”
Section: Multiple Myeloma (Mm) and Osteosarcomamentioning
confidence: 99%